Meaningful insights from raw metrics virtual worlds and other business applications - Yee, Nicholas; Ducheneaut, Nic.; Safari eBooks; O'Reilly strata making data work conference (2011 : Santa Clara, Calf.) ([S.l.] : O'Reilly, 2011)
"Virtual worlds are a goldmine of untapped insights, even for predicting physical behaviors. Not only will we share PARC findings and methods developed to extract key data from online games, but more importantly, we'll discuss how social scientists converted and processed raw behavioral metrics into meaningful psychological variables that can be applied to a broad spectrum of business applications."--Resource description page.
Title from title screen (viewed July 11, 2011).
Publication information from end credits.
Presenters, Nicholas Yee, Nic Ducheneaut.
Recorded at O'Reilly strata making data work conference: Feb. 1-3, 2011, Santa Clara, CA.
Keywords: Data mining; Computer games -- Social aspects; World of Warcraft; Interbehavioral psychology; Electronic books